Теория финансов предприятий: Учебное пособие / Д. С.Моляков, Е. И.Шохин - Моляков Д. С. (Финансы и статистика, 2000)
Экземпляры: (20200227) / Инвентарный номер: 36917 / Цена: 71.35 / Сис.шифр: 65.9(2)261.9 / Авт.знак: М76 / ГРНТИ: 10.21.21 / ББК: 65.9(2)261.9 я73